2020
DOI: 10.1002/pbc.28850
|View full text |Cite
|
Sign up to set email alerts
|

Cancer survivors exercise at higher intensity in outdoor settings: The GECCOS trial

Abstract: Purpose : This randomized cross‐over group pilot trial assessed feasibility of recruiting survivors from a long‐term follow‐up clinic to an exercise group and measured whether outdoor or indoor exercise sessions better supported exercise motivation and behaviors in survivors of cancer. Methods : Sixteen adolescent and young adult survivors of any cancer completed indoor and outdoor exercise sessions in this randomized cross‐over pilot trial. Measures of physical activity, motivation, and fatigue were taken 2 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(34 citation statements)
references
References 32 publications
0
34
0
Order By: Relevance
“…Similar benefits were observed in community gardening programme for obese adults 40 or farm-based day care for patients with dementia 41 . In a study of cancer survivors, however, outdoor exercises did not have greater impact on long-term physical activities than indoor exercises 42 . Among school students, nature-based activities did not increase moderate physical activity during play time more than playground sports 43 .…”
Section: Resultsmentioning
confidence: 76%
“…Similar benefits were observed in community gardening programme for obese adults 40 or farm-based day care for patients with dementia 41 . In a study of cancer survivors, however, outdoor exercises did not have greater impact on long-term physical activities than indoor exercises 42 . Among school students, nature-based activities did not increase moderate physical activity during play time more than playground sports 43 .…”
Section: Resultsmentioning
confidence: 76%
“…For all parallel-group trials, we used the RoB 2 version designed for individually randomized parallel-group trial designs, assessing the effect of assignment to interventions, i.e., "intention-to-treat". For one cluster-randomized, crossover trial [17], we used the RoB 2 tool supplements for cluster-randomized trials and for crossover trials.…”
Section: Risk Of Bias Assessmentmentioning
confidence: 99%
“…Six of the ten included trials were parallel-group randomized controlled trials [18,20,[27][28][29][30][31][32], whereas three studies were parallel-group controlled trials with no reporting of randomization [19,33,34]. One study was a cluster-randomized, counterbalanced crossover trial [17].…”
Section: Trial Design Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seeking solutions for mental restoration, researchers have demonstrated the benefits gained from natural environments and time spent outdoors [2,23,24]. There is increasing evidence concerning the positive effects of frequent exposure to natural environments [28,47,48]. For example, some have found that the increase of views toward nature can restore people from mental stress and fatigue and potentially improve their health and well-being [49,50], and this gives rise to additional benefits, such as attention restoration, sense of connectedness, companionship, and self-esteem [51].…”
Section: Literature Reviewmentioning
confidence: 99%